Behavioral And Sociodemographic Correlates Of Breast Self-Examination Among Women Of Reproductive Age - Singh, Anju; Divya, Divya; Jain, Prerna; Singh, Garima; Singh, Dinesh Kumar (Journal of Neonatal Surgery, 2025)
Background: Breast cancer remains a leading cause of morbidity and mortality among women globally, with an increasing trend in low- and middle-income countries, including India. 1 Early detection plays a pivotal role in reducing breast cancer mortality, and among the various screening modalities, Breast Self-Examination (BSE) is widely promoted as a cost-effective, non-invasive, and empowering technique, especially in resource-limited settings. Material & Methods: A cross-sectional study was conducted from August 2024 to July 2025 in a tertiary care hospital in north India among the study subjects reporting in out patient department of Gynecology for either of the condition among women of reproductive age (15–49 years). A single population proportion formula was used to determine the sample size for the quantitative data. A sample size of 250 was calculated based on an estimated proportion of BSE practice of 53.6% 7 .Data were collected using a standardized, pre-tested questionnaire, Face-to-face interviews were conducted for obtaining the desired information moderated by trained female facilitators. Results: An increasing trend of BSE practice with age among women of reproductive age was observed. Higher educational status is significantly associated with increased BSE practice. Among participants who had education up to high school or above, 52% reported practicing BSE regularly, compared to only 18% among those with less education. Married women are more likely to perform BSE (45%) compared to unmarried women (26%). Women who are knowledgeable about BSE show significantly higher practice rates (56%) compared to those who are not (15%). Conclusion: Educational status, age, marital status, employment, and knowledge about breast cancer were found to be significantly associated with BSE behavior. Additionally, psychological and cultural factors influenced BSE uptake, indicating that knowledge alone is insufficient to foster regular practice